2002
DOI: 10.1200/jco.2002.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Fulvestrant, Formerly ICI 182,780, Is as Effective as Anastrozole in Postmenopausal Women With Advanced Breast Cancer Progressing After Prior Endocrine Treatment

Abstract: Fulvestrant was as effective as anastrozole. These data confirm that fulvestrant is an additional, effective, and well-tolerated treatment for advanced breast cancer in postmenopausal women whose disease progressed on prior endocrine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
325
1
15

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(356 citation statements)
references
References 16 publications
15
325
1
15
Order By: Relevance
“…1993, Lykkesfeldt et al . 1994, 1995); further, fulvestrant was comparable to aromatase inhibitors in clinical efficacy in postmenopausal women having progressed on tamoxifen therapy (Howell et al . 2002, Osborne et al .…”
Section: Serms Vs Serds: Two Separate Classes Of Antiestrogens?mentioning
confidence: 99%
“…1993, Lykkesfeldt et al . 1994, 1995); further, fulvestrant was comparable to aromatase inhibitors in clinical efficacy in postmenopausal women having progressed on tamoxifen therapy (Howell et al . 2002, Osborne et al .…”
Section: Serms Vs Serds: Two Separate Classes Of Antiestrogens?mentioning
confidence: 99%
“…Data from preclinical model systems investigating initially endocrine sensitive BC cells subjected to long term anti-estrogen therapy has revealed that there are several stages of acquired resistance with an over-time shift in ER as well as growth factor expression [12]. Patients with acquired resistance might benefit from other types of endocrine intervention as estrogen withdrawal or therapy with the pure antiestrogen fulvestrant [13][14], contrary to patients likely to develop intrinsic resistance, for which endocrine therapy alone should be avoided. Our aim was to investigate intratumoral levels of VEGFR2 and downstream activated p38 MAPK (referred to as p38) in relation to previously determined intratumoral VEGF levels, routine breast cancer factors, localization of relapses and survival in receptor positive patients subjected to adjuvant endocrine treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent trials investigated the use of fulvestrant in second-line therapy. Two trials reported an effectiveness equivalent to that of anastrozole [21]. In the context of the randomized phase-III EFECT trial, the effectiveness of fulvestrant in metastatic breast cancer patients who had been pre-treated with nonsteroidal AI's was compared to that of exemestane [15].…”
Section: Discussionmentioning
confidence: 99%